2019
DOI: 10.1007/s11218-019-09510-9
|View full text |Cite
|
Sign up to set email alerts
|

Being stable and getting along with others: perceived ability expectations and employability among Finnish university students

Abstract: The aim of this study was to examine what sort of ability expectations university students have about the requirements of working life, and how the perception of these expectations relate to students' perceptions of their own employability. The participants comprised a sample of students (N = 1819) from two Finnish universities, representing diverse fields of study. They were asked to describe themselves according to a set of abilities and to then indicate those abilities that would be particularly important f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…The results confirmed that the self-efficacy influenced employability of the youth from marginalised communities. It is noted that the self-efficacy was correlated with employability in the model which is supported by previous research (Ahmed, Nawaz, & Rasheed, 2019;Chow, Wong, & Lim, 2019;Räty et al, 2019;Sultana & Malik, 2020;Tentama & Nur, 2021). Previous studies have proven that self-efficacy is positively related to employability (Ahmed et al, 2019;Liu, Cheng, Hu, Pan, & Zhao, 2020;Zhao, Peng, & Liu, 2021;Zhong, Qian, & Wang, 2020).…”
Section: Influence Of Personal Variables On the Employability Among Y...supporting
confidence: 84%
“…The results confirmed that the self-efficacy influenced employability of the youth from marginalised communities. It is noted that the self-efficacy was correlated with employability in the model which is supported by previous research (Ahmed, Nawaz, & Rasheed, 2019;Chow, Wong, & Lim, 2019;Räty et al, 2019;Sultana & Malik, 2020;Tentama & Nur, 2021). Previous studies have proven that self-efficacy is positively related to employability (Ahmed et al, 2019;Liu, Cheng, Hu, Pan, & Zhao, 2020;Zhao, Peng, & Liu, 2021;Zhong, Qian, & Wang, 2020).…”
Section: Influence Of Personal Variables On the Employability Among Y...supporting
confidence: 84%
“…In comparison, the Finnish group related only their future aspirations to external factors and assessment as it is presented in this configural model of CFA. This could be due to the fact that Finnish students associate to some extent academic skills along with other skills with employability (Räty et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Graduate employability has been on the global agenda for a couple of decades (see, e.g., Bennett, 2019; Crebert et al, 2004; Harvey, 2001; Laalo et al, 2019; Räty et al, 2019). This has occurred because of HE massification policies, which do not match employers’ demands and, in most cases, translate into an oversupply of graduates to the market (Bennett, 2019; Guile, 2009; Mok & Qian, 2018).…”
Section: Graduate Employability: Global Overviewmentioning
confidence: 99%